2017
DOI: 10.1080/01691864.2017.1396250
|View full text |Cite
|
Sign up to set email alerts
|

The role of quantitative information about slip and grip force in prosthetic grasp stability

Abstract: Prosthetic hands introduce an artificial sensorimotor interface between the prosthesis wearer and the environment, that is prone to perturbations. We analyze theoretically and evaluate psychophysically the performance in stable grip control in conditions of physical grasps perturbation, such as object slip. Simulation results suggest that user-centered stable grasp control depends on two primal user parameters: reaction time to slip and grip force intensity. Experiments with human users indicate that a user's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For the last several decades, researchers have been attempting to restore haptic feedback in upper-limb prostheses (see 2018 review by Stephens-Fripp et al 5 ). In particular, significant effort has been placed on the use of mechanotactile stimulations on the skin to provide prosthesis wearers with cues like grip force, grip aperture, and object slip [6][7][8] . Prior research has demonstrated the benefits of haptic feedback in improving discriminative and dexterous task performance with a myoelectric prosthesis [9][10][11][12] .…”
Section: Haptic Shared Control Improves Neural Efficiency During Myoe...mentioning
confidence: 99%
“…For the last several decades, researchers have been attempting to restore haptic feedback in upper-limb prostheses (see 2018 review by Stephens-Fripp et al 5 ). In particular, significant effort has been placed on the use of mechanotactile stimulations on the skin to provide prosthesis wearers with cues like grip force, grip aperture, and object slip [6][7][8] . Prior research has demonstrated the benefits of haptic feedback in improving discriminative and dexterous task performance with a myoelectric prosthesis [9][10][11][12] .…”
Section: Haptic Shared Control Improves Neural Efficiency During Myoe...mentioning
confidence: 99%
“…For the last several decades, researchers have been attempting to restore haptic feedback in upper-limb prostheses (see 2018 review by Stephens-Fripp, Alici, & Mutlu 5 ). In particular, significant effort has been placed on the use of mechanotactile stimulations on the skin to provide prosthesis wearers with cues like grip force, grip aperture, and object slip [6][7][8] . Prior research has demonstrated the benefits of haptic feedback in improving discriminative and dexterous task performance with a myoelectric prosthesis [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%